2008
DOI: 10.1111/j.1538-7836.2008.02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of circulating endothelial cells in vasculitis: comparison of flow cytometry and immunomagnetic bead extraction

Abstract: , 95% CI ±460 CECs mL )1 (P = 0.018). We identified three reasons for this discrepancy: (i) sub-optimal FC gating parameters previously used for detecting CECs; (ii) inherent lack of sensitivity of FC compared with IBE for CEC rare event detection; and (iii) use of lysis buffers required for FC causing CEC lysis. Conclusions: There was poor agreement between EC-optimized FC and IBE for the quantification of CECs from children with active vasculitis and controls. We emphasize that in this clinical setting the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…We also measured CECs with immunomagnetic bead extraction as supporting evidence of endothelial injury due to active vasculitis, using the consensus protocol previously described by ourselves and others. 27,42 mAbs and Reagents…”
Section: Study Populationmentioning
confidence: 99%
“…We also measured CECs with immunomagnetic bead extraction as supporting evidence of endothelial injury due to active vasculitis, using the consensus protocol previously described by ourselves and others. 27,42 mAbs and Reagents…”
Section: Study Populationmentioning
confidence: 99%
“…11,12,15 Importantly, CEC levels are predominantly affected by disease activity and endothelial injury and not treatment per se. 11,12,15 Our study now suggests that elevated CECs, and therefore persistence of endothelial injury, vary between children with single and recurrent AIS. CECs could therefore be an attractive candidate biomarker to detect those at risk of recurrent AIS, a finding that is consistent with the strong correlation between CECs and disease activity in systemic vasculitis.…”
mentioning
confidence: 99%
“…CECs were identified with immunomagnetic bead extraction based on an international consensus protocol. 11,24 CECs were defined as Ulex europaeus lectin (Sigma-Aldrich) bright cells .10 mm in size, with .5 magnetic beads attached (figure e-1A). 11,15,24 Cell-derived microparticles.…”
mentioning
confidence: 99%
“…Duda et al (17 ) proposed a cytometry protocol for phenotypic identification and enumeration of CECs and other cells in the blood, which has been adopted (6 ). However, in specific clinical setting, the agreement of the counts of CECs from the 2 techniques would be poor (3 ). Although flow cytometry is capable of high throughput and multiparametric analysis, capital and operational costs might prohibit its usage in resource-limited regions.…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Reports have indicated that the amount of CECs can serve as an indicator of the health of blood vessels, and this finding has been leveraged to monitor cardiovascular events (1,2 ) and vascular disease (3,4 ). Nozaki et al (1 ) presented an assessment of endothelial dysfunction by plasma concentrations of endotheliumderived microparticles.…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%